Monitoring vigabatrin in head injury patients by cerebral microdialysis: obtaining pharmacokinetic measurements in a neurocritical care setting. (November 2014) - Shannon, Richard J.; Timofeev, Ivan; Nortje, Jürgens; Hutchinson, Peter J.; Carpenter, Keri L. H.
<x xml:space="preserve">Abstract</x> Aims The aims were to determine blood–brain barrier penetration and brain extracellular pharmacokinetics for the anticonvulsant vigabatrin (VGB; γ‐vinyl‐γ‐aminobutyric acid) in brain extracellular fluid and plasma from severe traumatic brain injury (TBI) patients, and to measure the response of γ‐aminobutyric acid (GABA) concentration in brain extracellular fluid. Methods Severe TBI patients (n = 10) received VGB (0.5 g enterally, every 12 h). Each patient had a cerebral microdialysis catheter; two patients had a second catheter in a different region of the brain. Plasma samples were collected 0.5 h before and 2, 4 and 11.5 h after the first VGB dose. Cerebral microdialysis commenced before the first VGB dose and continued through at least three doses of VGB. Controls were seven severe TBI patients with microdialysis, without VGB. Results After the first VGB dose, the maximum concentration of VGB (Cmax) was 31.7 (26.9–42.6) μmol l−1 (median and interquartile range for eight patients) in plasma and 2.41 (2.03–5.94) μmol l−1 in brain microdialysates (nine patients, 11 catheters), without significant plasma–brain correlation. After three doses, median Cmax in microdialysates increased to 5.22 (4.24–7.14) μmol l−1 (eight patients, 10 catheters). Microdialysate VGB concentrations were higher close to focal lesions than in distant sites. Microdialysate GABA concentrations increased modestly in some of the patients after VGB administration. Conclusions Vigabatrin, given enterally to severe TBI patients, crosses the blood–brain barrier into the brain extracellular fluid, where it accumulates with multiple dosing. Pharmacokinetics suggest delayed uptake from the blood.